Modeling tumor relapse using proliferation tracing and ablation transgenic mouse - Chuang Zhao; Xin-nan Zheng; Han-ying Huang; Lin Tian (npj Breast Cancer)
Abstract Tumor relapse remains a significant obstacle to successful therapy. Preclinical animal models that accurately reflect tumor relapse in patients are urgently needed. Here, we employed a dual recombinase-mediated genetic system to genetically trace and ablate proliferating cells in a polyomavirus middle T antigen (PyMT)-induced spontaneous murine breast cancer model. This system enabled the acute ablation of cells that had undergone proliferation within a defined time window, resulting in a drastic tumor shrinkage, followed by a gradual tumor relapse due to the presence of residual low-cycling cells. We then applied single-cell RNA sequencing (scRNA-seq) to unbiasedly compare the tumor ecosystems of the primary and relapsed PyMT tumors. Compared with the primary tumors, the relapsed tumors exhibited a higher proportion of cancer stem cells and pro-tumor γδ T cells, as well as co-expression of Spp1 and Vegfa in multiple myeloid cell populations – features that predict poor therapeutic response and unfavorable outcomes in human breast cancer patients. Collectively, this proliferation tracing and ablation model emulates chemotherapies that preferentially eliminate proliferating cancer cells, serving as a robust tool and a valuable resource for testing novel therapeutic strategies in relapsed tumors.